Evaluasi Pelaksanaan Program Pencegahan Stunting di Era Pandemi Covid-19 - Wahyuni Arumsari; Dina Supriyati; Putri Sima (Jurnal Manajemen Kesehatan Indonesia, 2022)
The Covid-19 pandemic has disrupted all aspects of government activities through the implementation of PPKM. The implementation of community-based health programs has been delayed. This qualitative study aims to evaluate the implementation of the stunting prevention program during the COVID-19 pandemic. The study was conducted in Demak Regency, which has ten villages classified as stunting locus areas. Collecting data using in-depth interview method to five nutrition program holders at primary healthcare in the locus area. The data processing method uses content analysis. The stunting prevention programs studied included: promotion and counseling of infant and child feeding, supplementary feeding for severely malnourished and stunted toddlers, monitoring of toddlers' growth through posyandu activities, and administration of anthelmintic, vitamin A and supplementation for stunted under-fives. Based on the research, it is known that the stunting prevention program is constrained from the input components including limited health human resources resulting in a high workload; distribution of Vitamin A and helminths is carried out from door to door, and calibration of growth measuring instruments for toddlers is not routinely carried out. other constraints also occur in-process components, including program actuation due to PPKM activities from January to July 2021 by the central and regional governments; and monitoring of malnourished and stunting toddlers at the beginning of the pandemic.